Fabrication and characterization of porous scaffolds for bone replacements using gum tragacanth - Anita Lett, J.; Sundareswari, M.; Ravichandran, Kulandaivelu; Latha, Bavani; Sagadevan, Suresh (Elsevier, 2019)
The practice of bone implants is the standard procedure for the treatment of skeletal fissures, or to substitute and re-establish lost bone. A perfect scaffold ought to be made of biomaterials that duplicate the structure and properties of natural bone. However, the production of living tissue constructs that are architecturally, functionally and mechanically comparable to natural bone is the major challenge in the treatment and regeneration of bone tissue in orthopaedics and in dentistry. In this work, we have employed a polymeric replication method to fabricate hydroxyapatite (HAP) scaffolds using gum tragacanth (GT) as a natural binder. GT is a natural gum collected from the dried sap of several species of Middle Eastern legumes of the genus Astragalus, possessing antibacterial and wound healing properties. The synthesized porous HAP scaffolds were analyzed structurally and characterized for their phase purity and mechanical properties. The biocompatibility of the porous HAP scaffold was confirmed by seeding the scaffold with Vero cells, and its bioactivity assessed by immersing the scaffold in simulated body fluid (SBF). Our characterization data showed that the biocompatible porous HAP scaffolds were composed of highly interconnecting pores with compressive strength ranging from 0.036 MPa to 2.954 MPa, comparable to that of spongy bone. These can be prepared in a controlled manner by using an appropriate binder concentration and sintering temperature. These HAP scaffolds have properties consistent with normal bone and should be further developed for potential application in bone implants.